Impact of an acute geriatric outreach service to residential aged care facilities on hospital admissions. Issue 3 (5th September 2021) - Dai, Jun; Liu, Frank; Irwanto, Deni; Kumar, Manoj; Tiwari, Nabaraj; Chen, Jack; Xu, Yinghua; Smith, Matthew; Chan, Daniel KY
Abstract: Introduction: Residential aged care facility (RACF) residents frequently present to the emergency department (ED) and are often admitted to hospital. Some presentations and admissions may be avoidable. In 2013, Bankstown‐Lidcombe Hospital introduced a subacute geriatric outreach service (SGOS), which had little impact on reducing ED presentations. In 2015, Bankstown‐Lidcombe Hospital introduced an acute geriatric outreach service (AGOS), a geriatrician‐led team that assesses and treats acutely unwell patients in RACFs. We aim to determine whether the AGOS reduces the risk of hospital admission for RACF residents. Methods: Hospital admissions data from 2010 to 2019 were used to conduct an interrupted time series (ITS) analysis. AGOS activity data were also summarized. Results: The average number of admissions from RACF per month declined from 42.8 during the SGOS period to 27.1 during the AGOS period. The difference of 15.7 admissions from RACF per month was statistically significant (95% CI 12.1–19.2; P < .001). After the introduction of the AGOS, the risk of admission to our geriatric department from RACFs was reduced by 36.1% (incidence rate ratio =0.64; 95% CI: 0.58–0.71; P < .001) compared to the SGOS period, adjusting for seasonality. Discussion: The AGOS probably reduced the risk of hospital admission for RACF residents. Abstract : Monthly number of geriatric admissions to Bankstown‐Lidcombe Hospital from residential aged care facilities (2010–2019) 1. Subacute Geriatric Outreach Service introduced 2. Acute Geriatric Outreach Service introduced 3. 36% reduction in risk of hospitalization from RACF